If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7m + 16)(7 + -16) = 0 Reorder the terms: (16 + 7m)(7 + -16) = 0 Combine like terms: 7 + -16 = -9 (16 + 7m)(-9) = 0 Reorder the terms for easier multiplication: -9(16 + 7m) = 0 (16 * -9 + 7m * -9) = 0 (-144 + -63m) = 0 Solving -144 + -63m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '144' to each side of the equation. -144 + 144 + -63m = 0 + 144 Combine like terms: -144 + 144 = 0 0 + -63m = 0 + 144 -63m = 0 + 144 Combine like terms: 0 + 144 = 144 -63m = 144 Divide each side by '-63'. m = -2.285714286 Simplifying m = -2.285714286
| 2x+3-4x=5x-6 | | 6x+108=9x | | -3x(3x+8)(x-5)=0 | | 9y+5=17 | | 5x+9=-46-6x | | 2x-3=-5(x-4) | | 5(x-3)-(3x-7)= | | 18x^2-27x=3x^3 | | -x^8+(8x)-24=0 | | -3(k-7)(8k+3)=0 | | -2(x+2)=2(-x-1) | | 2cos(t)= | | 8iz^2+16=0 | | 9h-28=35 | | 19(39-2x)=703 | | 21x-10=5(4x+5)-15 | | 3r-4=4r-3 | | 8b-4b-b=55 | | 2n^2(n+6)(n-3)=0 | | 2f+7=8f-23 | | 25x^2+30x=5x^3 | | h(h+4)=3(h-2)+12 | | 3h-1=5h-21 | | 8m-14=50 | | -9x+y=-19 | | f(x)=-6x^2+9x+7 | | 7p+13=6p+16 | | 451=540x | | V=3.14(36)(14) | | 4(2x+3)=7(3x-2) | | 10y-4=5y+6 | | H^2-6+h=0 |